THE EFFECT OF PEER INTERACTION TOWARDS STUDENTS LEARNING MOTIVATION OF RELIGIOUS PROGRAM AT MAN JOMBANG - Leni Fadilatur Rohmah; Khoirul Umam (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Students in the world of education will have social interactions. Friends are the first environment for children or adolescents after the family environment in learning to interact socially. Peer interactions can develop your potential. However, not all peer interactions have a positive impact on students, especially encouragement to learn. Therefore, this research aims to determine the influence of peer interactions on students' learning motivation. This research uses a quantitative research approach with an ex-post facto type of research. The population in this study were students of the MAN 4 Jombang Religious Program (PK) for the 2023/2024 academic year, a total of 144 students. The sampling technique used proportional random sampling to obtain a total of 36 students. Data collection techniques use observation, questionnaires and documentation. Test the validity of the instrument using Person Product Moment correlation and test reliability using the Cronbach's Alpha formula. Meanwhile, prerequisite analysis tests include normality tests, homogeneity tests, linearity tests, correlation tests and hypothesis tests which include simple linear regression equations. The results of the simple linear regression test produce the influence of peer interactions on student learning motivation. The magnitude of the influence is 57% while the rest is influenced by other variables not included in this model.